What are the main barriers to achieve minimal disease activity in psoriatic arthritis in real life? - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2019)
Objective Minimal disease activity (MDA) is an important target in patients with psoriatic arthritis (PsA), however it is also criticised for having a low threshold for patient reported outcomes (PRO). The aim of the study was to assess the prevalence of MDA and its components in patients with PsA and to evaluate disease characteristics and patterns in patients with or without MDA (MDA(+) or MDA(-)). Methods PsArt-ID (Psoriatic Arthritis-International Database) is a prospective, multicentre web-based registry. PsA patients who had at least 1 year of disease duration and had full data for MDA were included for this analysis (n=317). Patients were considered in MDA+ when they met at least 5/7 of the MDA criteria. Results MDA was achieved in 46% patients. Within MDA- patients, body surface area (51.2%) and swollen joint count (53.5%) domains could still be achieved in the majority and 93.5% of them had no enthesitis using the Leeds enthesitis index. Of 170 patients with MDA-, 90 patients did not fulfill all 3 PROs of MDA. Mono-arthritis subtype (RR: 2.01), absence of enthesitis (RR: 1.570) and absence of distal interphalangeal (DIP) joint disease (RR: 1.1) were associated with higher probability of achieving MDA. Conclusion The MDA criteria provide an objective target for treatment in trials and clinical practice; however, in real life PROs are the most significant barriers to achieve MDA. The presence of DIP joints disease makes it difficult to reach MDA due to active PROs.
Keywords: psoriatic arthritis; minimal disease activity; patient-reported outcomes; PREDICTORS; CRITERIA